Perlindungan Hukum terhadap Penyewa Mobil yang di Asuransikan dalam Perjanjian Sewa-Menyewa Mengalami Kecelakaan di Kota Medan: Studi Kasus PT Berkah Travel dan Tour Medan - Candra Saputra Siregar; Adlin Budhiawan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This research aims to analyze legal protection for car renters in rental agreements who experience accidents in Medan City, by taking the case study of PT Berkah Travel and Tour. The research method used is an empirical legal method with a case approach, with data collection techniques, literature studies, interviews with related parties. In answering the problem, a case approach and a statue approach were used. Based on research, it can be seen that PT Berkah Travel and Tour insures each car unit, and provides protection for the driver. However, there are several limitations and requirements that need to be met by renters to be able to take advantage of this insurance. Apart from that, several obstacles were found in implementing this legal protection, such as complex claim procedures and quite long claim settlement times. This research discusses legal protection for insured car renters.